Addressing low technical competency of state medicaid content developers: An action research on building enabling work process through performance pathway and gap analysis - Hernandez, John Michael H. (Animo Repository, 2021)
This Integrated Action Research addressed the issue of low technical competency of State Medicaid Content Developers of Your Healthcare Inc. with the overall goal of developing a sustainably technically competent developers. This paper specifically aims to enhance the members technical execution skills and improve the quality of their output through coupling effective training and development with supportive and enabling job resources and processes. The issue was identified with the use of action research tools including ORJI, ladder of inference, and lefthand column, through collaboration with team members using levels of inquiry, systems mapping, and force field analysis, and through the utilization of internal company data. Guided by the Performance Pathway Model and Gap Analysis, we implemented the use of a policy development tool as a supportive resource and a calibration process as an educational access to improve the content developers’ performance. Moreover, Lewin’s Unfreeze-Change-Refreeze model guided the implementation of changes made throughout the conduct of the action research. With consistent collaboration and commitment, the Content Developers were able to adapt to changes allowing them to meet, even surpass, the level of performance expected of them.